A combination of paclitaxel and gemcitabine in an intensive dose-dense neoadjuvant chemotherapy schedule for locally advanced breast cancer - I. V. Frai; N. I. Perevodchikova; V. P. Letyagin; V. A. Gorbunova; O. A. Anurova (Опухоли женской репродуктивной системы)
Objective: to improve the results of neoadjuvant chemotherapy (CT) in patients with locally advanced (L A) inoperable breast cancer (BC) at baseline, by using the intensified combination CT at the interval being reduced between the administration of cytostatic dru gs to 2 weeks to give a chance to the patients to be surgically treated.Subjects and methods. The study enrolled 26 patients aged 33 to 75 years with L A BC. Paclitaxel was administered intravenously (IV) over 3 hours at a dose of 175 mg/m2 on day 1, followed by gemcitabine, 2000 mg/m2, given by 30-minute IV infusion on day 1 every 2 w eeks. If the cytostatics were well tolerated and their effect increased, the treatment was continued up to 6 courses.Results. Eighteen (69.2%) out of the 26 patients achieved the objective effect of treatment; of them 17 (65.4%) had a partial remission and 1 (3.8) had a complete remission.The therapeutic pathomorphism of a tumor w as rated in 22 patients; fourth-degree tumor pathomorphism w as found in 2 (9%) patien ts. The follow-up of patients w as 11 to 28 months (median, 20 months). The median time to progression w as not reached in the entire group of patients.Conclusion. A combination of paclitaxel and gemcitabine in intensive dose-dense scheduling has a marked antitumor activity in BC andis characterized by its good tolerability without a pronounced myelosuppressive effect. This therapy regimen may be used as neoadjuvant CT.